2017
DOI: 10.5194/amt-10-3325-2017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal estimation of water vapour profiles using a combination of Raman lidar and microwave radiometer

Abstract: Abstract. In this work, a two-step algorithm to obtain water vapour profiles from a combination of Raman lidar and microwave radiometer is presented. Both instruments were applied during an intensive 2-month measurement campaign (HOPE) close to Jülich, western Germany, during spring 2013. To retrieve reliable water vapour information from inside or above the cloud a two-step algorithm is applied. The first step is a Kalman filter that extends the profiles, truncated at cloud base, to the full height range (up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The exponential component accounts for the different attenuation of the returned signal with α(r, λ N 2 /H 2 O ), including both the molecular and the particle contribution. In this paper the particle extinction contribution is neglected as the resulting error is less than 1.3 % at 2 km altitude as calculated by Foth et al (2015). Whiteman (2003) concluded that such assumption can introduce an error of approximately 2 % for every 0.5 of aerosol optical depth change below 2 km altitude.…”
Section: Wvmr Profiles From Raman Lidar Signalsmentioning
confidence: 94%
See 3 more Smart Citations
“…The exponential component accounts for the different attenuation of the returned signal with α(r, λ N 2 /H 2 O ), including both the molecular and the particle contribution. In this paper the particle extinction contribution is neglected as the resulting error is less than 1.3 % at 2 km altitude as calculated by Foth et al (2015). Whiteman (2003) concluded that such assumption can introduce an error of approximately 2 % for every 0.5 of aerosol optical depth change below 2 km altitude.…”
Section: Wvmr Profiles From Raman Lidar Signalsmentioning
confidence: 94%
“…The second approach determines the calibration factor using simultaneous measurements from a collocated reference instrument. Approaches on this second technique include water vapor comparisons with radiosondes, satellites and microwave radiometers (Ferrare et al, 1995;Mattis et al, 2002;Miloshevich et al, 2004;Madonna et al, 2011;Leblanc et al, 2012;Reichardt et al, 2012;Navas-Guzmán et al, 2014;Foth et al, 2015). The accuracy of the calibration factor derived using these techniques fluctuates between 5 and 10 %.…”
Section: Lidar Water Vapor Calibration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the potential usefulness of the MRL-measured data for weather forecasting, the MRL cannot measure the water vapor inside and above optically thick clouds. To overcome this disadvantage, it is important to use synergistic approaches with different instruments such as GNSS, microwave radiometer, and radiosonde to measure the water vapor distribution even under cloudy conditions (e.g., Foth and Pospichal, 2017).…”
Section: Vertical Distributionsmentioning
confidence: 99%